2021
DOI: 10.1001/jama.2021.8240
|View full text |Cite
|
Sign up to set email alerts
|

The US Preventive Services Task Force Recommendation on Lung Cancer Screening

Abstract: and receiving personal fees and equity from Nava Health. No other disclosures were reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 4 publications
1
56
0
Order By: Relevance
“…Regarding the demise of this 75-year-old male farmer who presented with features of advanced bronchogenic carcinoma with secondary liver metastasis and sepsis on his initial visit to the hospital, this shows the falling standard of preventive care in a typical developing country, as this patient did not benefit from the required regular personal interaction from a primary caregiver, his prevailing risk factor was not discussed, smoking cessation interventions were not offered, and periodic screening for bronchogenic carcinoma was not done. This is in contrast with the measures taken in developed countries, especially in the US, where the United States Preventive Services Task Force (USPSTF) recommends screening for lung cancer with low-dose computed tomography (CT) scan every for adults aged 50 to 80 years who have a 20 pack-year smoking history and currently smoke or have quit smoking within the past 15 years, and discontinuation of screening once a person has not smoked for 15 years or has a health problem that limits life expectancy or the ability to have a lung surgery [11].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the demise of this 75-year-old male farmer who presented with features of advanced bronchogenic carcinoma with secondary liver metastasis and sepsis on his initial visit to the hospital, this shows the falling standard of preventive care in a typical developing country, as this patient did not benefit from the required regular personal interaction from a primary caregiver, his prevailing risk factor was not discussed, smoking cessation interventions were not offered, and periodic screening for bronchogenic carcinoma was not done. This is in contrast with the measures taken in developed countries, especially in the US, where the United States Preventive Services Task Force (USPSTF) recommends screening for lung cancer with low-dose computed tomography (CT) scan every for adults aged 50 to 80 years who have a 20 pack-year smoking history and currently smoke or have quit smoking within the past 15 years, and discontinuation of screening once a person has not smoked for 15 years or has a health problem that limits life expectancy or the ability to have a lung surgery [11].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, lung cancer patients face a poor prognosis, with a five-year survival rate of only 21% [3]. To improve patient outcomes by identifying cancer early, the US Preventative Services Task Force recommends high-risk adults over 50 years old to undergo yearly screening with low dose computed tomography (LDCT) [4]. Survival analysis, or the estimation of time until death, from a lung cancer patient's LDCT scans can help plan patient care and management.…”
Section: Introductionmentioning
confidence: 99%
“…The US Preventative Services Task Force (USPTF) has recommended routine low-dose computed tomography (LDTC) LC screening of a defined population of high risk individuals ( 4 ). The USPTF however found that LDTC screening was associated with harms which included high false positive rates resulting in unnecessary tests and invasive procedures, incidental non-cancerous findings, overdiagnosis and radiation exposure.…”
Section: Introductionmentioning
confidence: 99%
“…The USPTF however found that LDTC screening was associated with harms which included high false positive rates resulting in unnecessary tests and invasive procedures, incidental non-cancerous findings, overdiagnosis and radiation exposure. They therefore called for more research to develop biomarkers to improve the detection rate and lower the false positive rate of LDTC screening ( 4 ).…”
Section: Introductionmentioning
confidence: 99%